Target Transportation of Auxin on Mesoporous Au/SiO2 Nanoparticles as a Method for Somaclonal Variation Increasing in Flax (L. usitatissimum L.). (9th February 2017) - Kokina, Inese; Jahundoviča, Inese; Mickeviča, Ilona; Jermaļonoka, Marija; Strautiņš, Jānis; Popovs, Sergejs; Ogurcovs, Andrejs; Sledevskis, Eriks; Polyakov, Boriss; Gerbreders, Vjačeslavs
Abstract : Development of methods for direct delivery of different bioactive substances into the cell is a promising and intensively approached area of research. It has become a subject of serious research for multidisciplinary team of scientists working in such areas as physics, biology, and biotechnology. Plant calluses were grown on medium supplemented with different nanoparticles to be used as a model for biotechnological research. Gold nanoparticles with mesoporous silica coating were used as hormone carriers, since they possess many of critical properties required for cellular transportation instrument. Some of those properties are great biocompatibility and controlled release of carried molecules. Significant changes in hormones common impact were detected. The great increase in ploidy numbers, embryogenesis, induction, and methylation level was observed when compared to the "conventional" methods of targeted hormones delivery that embrace usage of Au nanoparticles as a main hormone carrier. The authors suppose the research under consideration can provide a new pathway to the design of a novel targeted plant hormone and bioactive substances carrier.